PSYCHOLOGICAL AND PEDAGOGICAL ASPECTS OF RESEARCH INTO THE PROBLEM OF BILINGUAL FOREIGN LANGUAGE TEACHING (Conferencea, 2023)
Currently, it is legitimate to talk about the greater spread of a broad understanding of bilingualism as proficiency in varying degrees of two or more languages in both domestic and foreign linguistics. We emphasize that foreign researchers, speaking about the degree of language acquisition, suggest not to forget about the dynamic category of language skills, which are divided into two groups: productive (speaking and writing) and receptive (listening and reading). To assess the degree of mastery of the above skills and micro-skills (size of vocabulary, accuracy and correctness of grammatical structures used, etc.) a variety of tests are used that need to be revised in connection with the ever-increasing scale of globalization. The purpose of the article is formulated as follows: based on the experience of linguists, teachers, psychologists, and linguistic methodologists, to determine the most optimal methods of working with bilingual students for more successful learning of the foreign languages.